Draft Annual Plan 1989-90 Part-II-Plan Proposals in Details Government of Goa - Planning Commission (Planning Commission, 1988)
Objective for the Seventh Five Year Plan (1985-90) To strengthen the existing Agricultural Statistics machinery for collection and compilation of Statistical data, monitoring & evaluation of results of various schemes implemented by the Department and introduction of primary reporting system in the State.
Directorate of planning, Statistics and Evaluation
Directorate of planning, Statistics and Evaluation